PENGEMBANGAN CUSTOMER EXPERIENCE MANAGEMENT UNTUK MENCIPTAKAN LOYALITAS PELANGGANDALAM BISNIS RITEL - GITA, NYOMAN (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The aim of the paper is to provide understanding development of customer experience management to create customer loyalty in the retail business. Customer loyalty has an important role for retailers to face tight competition. The competition leads retailer to pursue customer loyalty..Customer experience management seeks to establish a good experience for customers while they was shopping. Customer experience management can be used for the retailer in order to create customer loyalty. Customer satisfaction experience is expected to bring as an indicator of customer loyalty. Development of customer experience management to create customer loyalty should be supported by things that can create better customer experience in shopping. Improving the quality of employees to serve customer is important to create customer loyalty through customer experience management. Key words: customer experience management, customer loyalty, retail business